2019
DOI: 10.4103/ijabmr.ijabmr_92_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of single-nucleotide polymorphisms of transcription factor 7-like 2 and ATP2B1 genes as cardiovascular risk predictors in chronic kidney disease

Abstract: Introduction:Cardiovascular disease (CVD) is the primary cause of morbidity and premature mortality in chronic kidney disease (CKD). The transcription factor 7-like 2 (TCF7L2) gene product TCF4 is a transcription factor that acts as a downstream effector in the canonical Wnt signaling pathway and may be important in the development of both type 2 diabetes and renal development and disease. It is, therefore, plausible that mutations in this gene could manifest themselves in reduced kidney function or kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…A previous study performed on a group of ESRD patients with CVD compared to a healthy control group found a significant association between the TCF7L2 gene rs7903146 and risk of CVD occurrence in ESRD patients [20], which supported our results. Another study done on a group of CKD patients compared to a group of healthy controls showed that the T allele of the TCF7L2 gene rs7903146 is a genetic risk factor for CVD in CKD patients [21], which also comes in accordance with our results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A previous study performed on a group of ESRD patients with CVD compared to a healthy control group found a significant association between the TCF7L2 gene rs7903146 and risk of CVD occurrence in ESRD patients [20], which supported our results. Another study done on a group of CKD patients compared to a group of healthy controls showed that the T allele of the TCF7L2 gene rs7903146 is a genetic risk factor for CVD in CKD patients [21], which also comes in accordance with our results.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are supported by a study performed on 2 groups of diabetic patients, one group with DKD and the other group without DKD, which found that patients harboring the TT genotype of rs7903146 were at higher risk to acquire the nephropathy than the CC genotype carriers (p = 0.02), elucidating that the T allele confers genetic risk to develop nephropathy and its complications such as CVD [22], which also come in accordance of our results. A recent study performed on CKD patients with CVD compared to healthy controls reported that the T allele of rs7903146 had a significant association with CVD development in CKD patients (OR = 2.2 and p < 0.05) [21]. Another study performed on ESRD with CVD compared to a group of healthy controls found that CKD patients carrying the T allele of rs7903146 in the TCF7L2 gene were 1.57 times more susceptible for developing CVD than C allele carriers (OR = 1.57 and 95 % CI = 1.31-1.90), which comes in harmony with the results of our study [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 28 ] Genome wide association studies and ATP2B1 knockout mouse studies have shown that ATP2B1 may play an important role in the regulation of blood pressure and hypertension through alterations of calcium handling and vasoconstriction in VSMCs. [ 29,30 ] ATP2B1 genomic regions have also been associated with hyperlipidemia and diabetes, [ 31 ] and in a recent study, ATP2B1 gene silencing increased insulin sensitivity in endothelial cells. [ 32 ] Furthermore, in a candidate gene association study, ATP2B1 was associated with coronary artery calcification in chronic kidney disease and myocardial infarction in the general population.…”
Section: Discussionmentioning
confidence: 99%